EU enlargement and (temporary) migration: Effects on labour market outcomes in Germany - Luisa Hammer; Matthias S. Hertweck (Deutsche Bundesbank, 2022)
EU Eastern Enlargement elicited a rise in (temporary) labour market oriented immi-gration to Germany starting in May 2011. Taking into account that not all immigrantsstay permanently and that outmigration flows are selective, this paper classifies recent EUimmigrants into 'new arrivals' and 'stayers' drawing on administrative social securitydata (2005-2017). This novel strategy allows us to separately identify their potentiallyopposing short- and medium-run effects on labour market outcomes in Germany. We finda transitory negative wage effect among German nationals, particularly at the bottom ofthe wage distribution; and a permanent positive effect on full-time employment.
Keywords: E24; F22; J31; J61; 330; EU Eastern Enlargement; immigration; wages; employment; Germany